Tracking Persons With Vehicles - Daiciu, Laura Silvana (Eximia, 2023)
In order to carry out an exhaustive investigation of the theme, the analysis of the problems was resorted to by referring to certain doctrinal points of view, evaluating and synthesizing some aspects in the field of technique and tactics of the tracking bodies. I used the inductive method as the main method because science uses experience as a means of confirming its conclusions and hypotheses. For the study of the theme, its complexity was taken into account, for which a combination of some classic research methods with some new method,s was preferred. Thus, direct observation was used to underline the importance of the methods/tactics/rules that must be followed so that the mission of tracking people can be a success. Indirect observation was used by appealing to some clear and well-written previous findings in the studied subject. Other methods used throughout the elaboration of the paper include: - the sociological method necessary for the collection, analysis and interpretation of information; - the documentary research undertaken at some police headquarters in order to fully understand the techniques and tactics of the investigative bodies; - the documentary research undertaken at the headquarters of the local police units to reveal the number of files, which were solved with the help of tracking techniques; - indirect research.